Ngirhaphium Evenhuis & Grootaert from southern Thailand (Diptera: Dolichopodidae) with the description of a new species - Samoh, Abdulloh; Boonrotpong, Singtoe; Grootaert, Patrick (Zootaxa, 2015)
The genus Ngirhaphium Evenhuis & Grootaert, 2002 is reported for the first time from Thailand in particular from mangroves on the coast of the Andaman Sea in southern Thailand. Three species were found: N. murphyi Evenhuis & Grootaert, 2002, N. sivasothii Grootaert & Puniamoorthy, 2014 and N. chutamasae sp. nov. The latter species is described and illustrated and a key to all four known species is provided. COI barcode data showed that the new species is most closely related to N. murphyi with a genetic distance of 7%. The distance with the other species is 11 to 12%.